Criminalizing Assault. The Failure of the Offence Against Society Model - Cretney, Antonia (The British journal of criminology, 1994)
The authors undertook a study of assault, starting outside the justice system with 93 assault victims admitted to the Accident and Emergency Department of a city-centre hospital. They found that in relation to this type of offence the police do not respond to crime'; they respond to complaints' from an aggrieved'. If the victim is too fearful or for some other reason is reluctant to co-operate with the prosecution effort, matters proceed no further. This does not conform to the offence against society' model of criminal justice advanced by academic commentators. In fact this model is applied at the court stage of the criminal process, when the victim interest may be neglected entirely, but not at the vitally important stage of police/victim interaction